Comparison of structure variants covering of storage building - Misiura, Ye. (Ways to Improve Construction Efficiency, 2024)
In connection with the constant increase in the volume and pace of freight transportation throughout the world, the creation of high-quality storage buildings is of particular importance. Unfortunately, in domestic practice, this aspect is given relatively little attention, and even specialized standards for the classification of building structures practically bypass this issue. However, in international practice, storage buildings are a more important construction object, which has a specialized classification based on a set of basic indicators. Moreover, the higher the class of the building, the higher its status and importance and, accordingly, the higher income it can bring to its owner. Therefore, the issue of upgrading the class of a storage building is quite relevant and significant. One of the parameters that directly affects the classiness of the storage building is the distance between the columns. In the course of the research, three structural variants of the roof of a storage building with a steel frame, located in the city of Dnipro, were considered. The variants differed in the construction of the supporting beam and provided the possibility of overlapping spans of 36 m, 24 m and 12 m with a total span of the storage area of 72 m. During the numerical analysis, the finite element method was used using the domestic design and calculation complex SCAD. As a result, it was established that the design variant using rafter trusses with a span of 24 m is more effective in terms of mass indicators than the variants for using rafter trusses with a span of 36 m (by 60 %) or beams with a span of 12 m (by 130 %). This made it possible to raise the class of the storage building according to the international classification from class B+ to class A. Detailed drawings were developed for the selected design option, which are planned for implementation in project practice.